Environmental heavy metal pollution and effects on child mental development risk assessment and prevention strategies - Simeonov, Lubomir; Kochubovski, Mihail V.; Simeonova, Biana G.; SpringerLink (Online service). (Dordrecht Springer, 2011)
They say metals can be emitted into environment by both natural and anthropogenic sources, mainly mining and industrial activity. Human exposure occurs through all environmental media. Infants are more susceptible to the adverse effects of exposure. Increasing attention is now being paid to the mental development of children exposed to heavy metals. The purpose of this book is to evaluate the existing knowledge on intellectual impairment in children exposed to heavy metals in their living environment and to identify the research needs in order to obtain a clearer picture of the situation in countries and regions at risk, in which the economy is closely related to metallurgy and heavy metals emission, and to recommend a strategy for human protection. In greater detail the main objectives could be formulated as follows: to review the principal sources of single, and complex mixtures of, heavy metal pollutants in the environment; to identify suitable methodology for chemical analyses in the environment and in humans; to evaluate the existing methods for measuring mental impairment, including their reliability and validity; to recommend a standard testing protocol to be used in future research; to assess the future role of environmental heavy metal pollution in countries and regions at risk and its effects on childrens neurological development; to recommend a prevention strategy for protecting childrens health and development.
Preface -- Acknowledgements -- List of contributors -- Environmental Heavy Metals and Mental Disorders of Children in Developing Countries -- Exposure Assessment to Heavy Metals in the Environment. Measures to Eliminate or Reduce the Exposure to Critical Receptors -- Heavy Metals Activity Mechanisms at Cellular Level and Possible Action on Children Bodies -- Evolving Understanding of the Relationship between Mercury Exposure and Autism -- Hearing Changes in Children Exposed to Arsenic in Neurotoxicity Context -- Lead Occurrence in Childrens Biological Fluids from Baia Mare Area, Romania -- Changing Children?s Blood Lead Level in Hungary -- Analytical Approaches for Sampling and Sample Preparation for Heavy Metals Analysis in Biological Materials -- Heavy Metals Determination in Environmental and Biological Samples -- Analyses of Heavy Metal Mixtures in the Environmental Media -- Atomic Absorption Spectrometry (flame, electrothermal, vapor generation) in Environmental, Biological, and Food Analysis -- In Situ Elemental and Isotopic Analyses of Heavy Metals in Environmental Water Solutions -- A Heavy Metal Environmental Threat Resulting from Combustion of Biofuels of Plant Origin -- Heavy Metals as Persistent Problem for Balkan Countries -- Assessment of Heavy Metal Contamination in Soils around Kremikovtzi Smelter (Bulgaria) -- Comparison Study of Physicochemical Parameters Evaluation between Danube River and AXIOS-VARDAR River Valley (2003-2009) -- Atmospheric Heavy Metals Pollution: Exposure and Prevention Policies in Mediterranean Basin -- The Problem of Heavy Metal Pollution in the Republic of Armenia: Overview and Strategies of Balancing Socioeconomic and Ecological Development -- How to Grow Environmentally-Sound Biofuels -- NATO Advanced Research Workshop on Environmental Heavy Metal Pollution and Effects on Child Mental Development Risk Assessment and Prevention Strategies: Discussion, Conclusions and Recommendations -- Subject Index.
Electronic reproduction.
Keywords: Heavy metals -- Environmental aspects; Heavy metals -- Physiological effect; Child psychopathology -- Environmental aspects; Electronic books